TUJUAN DAN PENERAPAN TEORI BEHAVIORISME DALAM PEMBELAJARAN - Kiki Mardiyani (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Behaviorism learning theory is a change in behavior as a result of the interaction between stimulus and response. Learning is a form of change experienced by students in terms of their ability to behave in new ways as a result of the interaction between stimulus and response. The figures of learning theory according to the understanding of each expert are Edward Lee Thorndike, Ivan Petrovic Pavlov, Vladimir M Bekhtereev, etc. There are advantages and disadvantages in this theory, so that the purpose of this theory is to emphasize the addition of knowledge, while learning is a "mimetic" activity that requires students to review the lessons they have learned in the form of reports, quizzes, and tests.